Pendampingan Open Lab Fisika Berbasis Microsoft Office Pada Sekolah Menengah Atas Islam Diponegoro - Muhammad Sayyadi; Moh Ahsan; Sholikhan (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2024)
Physics is a science that is directly related to daily life events. In studying physics in schools, it is inseparable from the role of laboratories as the main support for learning success, so it is necessary to have facilities and infrastructure in the form of practicum tools. For schools that do not have laboratories, it is necessary to collaborate with other agencies such as universities. The purpose of this service is in the form of Open Laboratory activities, namely providing practicum assistance to schools with inadequate equipment facilities. The Open Lab activity was carried out at SMA Islam Diponegoro with several stages, namely coordinating with teachers in the field of study about practicum needs, implementation schedules, preparation stages for modules to be used, practicum mentoring process, data analysis using excel and word and evaluation of activity results.. The average results of the pre-test were 102.71, the post-test was 146.37, and the N-Gain value was 0.60 with the medium category. This shows that there is a positive response from students due to the practicum. The results obtained in the service activities are the preparation of practicum modules, the creation of more meaningful learning. This service also received a good response from teachers and students.